Effect of Dietary Cold-Pressed Hempseed Cake Supplemented with Tomato Waste on Laying Hen Performance and Egg Yolk Lipid Profile and Antioxidant Status Before and After Storage - Daniel Mierlita; Stelian Daraban; Alin Cristian Teușdea; Alina Stefania Stanciu (Animals)
A ten-week study was conducted to investigate the effects of the dietary inclusion of HSC as a source of PUFAs together with a natural source of antioxidants such as DT or DTP on the performance of laying hens and egg quality, as well as the lipid profile, antioxidant content and oxidative stability of egg yolk before and after storage. A total of 96 laying hens (aged between 28 and 37 weeks) were divided into three groups of 32 birds each (eight replicate cages, four birds per cage) and were assigned randomly the following dietary treatments: a standard corn–soybean meal diet (C), a diet containing 20% hempseed cake and 4% dried whole tomato (HT) and a diet containing 20% hempseed cake and 4% dried tomato pomace (HTP). The incorporation of HSC and tomato waste (DT and DTP) into the diet of hens caused increases in feed intake (p < 0.05) and yolk color score without changing egg production, egg weight or feed conversion ratio (FCR). The HT and HTP diets ensured a lower content (p < 0.05) of cholesterol in the egg yolk but a higher content (p < 0.001) of n-3 FAs, especially of ALA (α-linolenic acid, 18:3n-3), EPA (eicosapentaenoic acid, 20:5n-3) and DHA (docosahexaenoic acid, 22:6n-3), which allowed for an increase in the hypo-/hypercholesterolemic FA ratio and a reduction in the n-6/n-3 FA ratio and TI (thrombogenicity index) value compared to those of C eggs. In addition, the inclusion of DT or DTP in the diet of laying hens increased the antioxidant content in the yolk, which led to an increase in the oxidative stability of the yolk lipids, evidenced by a decrease in the concentrations of MDA (malondialdehyde) in fresh eggs and those stored for 30 days at 4 °C. DTP exerted the most desirable effects because the egg yolk had the most intense color, the highest contents of n-3 FAs and natural antioxidants and the best oxidative stability of yolk lipids before and after egg storage. It was concluded that the simultaneous enrichment of the diet of laying hens with n-3 FAs and natural antioxidants (carotenoids, tocopherols and phenols), in addition to improving the color of the yolk, leads to eggs with a higher content of n-3 FAs and antioxidants, improved antioxidant activity and better PUFA stability during egg storage.